Forced expression of DYRK2 exerts anti-tumor effects via apoptotic induction in liver cancer. (1st June 2019) - Yokoyama-Mashima, Shiho; Yogosawa, Satomi; Kanegae, Yumi; Hirooka, Shinichi; Yoshida, Saishu; Horiuchi, Takashi; Ohashi, Toya; Yanaga, Katsuhiko; Saruta, Masayuki; Oikawa, Tsunekazu; Yoshida, Kiyotsugu
Abstract: Liver cancer is highly aggressive and globally exhibits a poor prognosis. Therefore, the identification of novel molecules that can become targets for future therapies is urgently required. We have reported that dual-specificity tyrosine-regulated kinase 2 (DYRK2) functions as a tumor suppressor by regulating cell survival, differentiation, proliferation and apoptosis. However, the research into its clinical application as a molecular target has remained to be explored. Here we showed that DYRK2 knockdown enhanced tumor growth of liver cancer cells. Conversely and more importantly, adenovirus-mediated overexpression of DYRK2 resulted in inhibition of cell proliferation and tumor growth, and induction of apoptosis both in vitro and in vivo . Furthermore, we found that liver cancer patients with low DYRK2 expression had a significantly shorter overall survival. Given the findings that DYRK2 regulates proliferation and apoptosis of cancer cells, DYRK2 expression could be a promising predictive marker of the prognosis in liver cancer. Stabilized or forced expression of DYRK2 may become thus a potential target for novel gene therapy against liver cancer. Highlights: DYRK 2 suppresses tumor growth ability of liver cancer. Adenovirus-mediated overexpression of DYRK2 induces apoptosis in tumor. Liver cancer patients with low DYRK2 expression have shorter overall survival.